齿轮修形参数对变速箱传动特性影响的研究 - 杨本洋; 褚超美; 汤海川; 缪国 (Jixie chuandong)
Focusing on the vibration and noise of gear transmission,taking Masta software as the analysis platform,by simulating and computing the modification of main reduction gear of a transmission,the effect relations between change of modification parameters such as tip relief,barreling relief and crowning relief with characteristic of gear transmission is obtained.The optimum modification parameters are selected based on the study of the law of gear transmission error and max contact pressure.Noise test result shows that the squeal of the transmission is reduced effectively after gear modification.